Improving abortion underreporting in the USA: a cognitive interview study. Issue 1 (2nd January 2023) - Mueller, Jennifer; Kirstein, Marielle; VandeVusse, Alicia; Lindberg, Laura D.
Abstract: Abortion is a difficult-to-measure behaviour with extensive underreporting in surveys, which compromises the ability to study and monitor it. We aimed to improve understanding of how women interpret and respond to survey items asking if they have had an abortion. We developed new questions hypothesised to improve abortion reporting, using approaches that aim to clarify which experiences to report; reduce the stigma and sensitivity of abortion; reduce the sense of intrusiveness of asking about abortion; and increase respondent motivation to report. We conducted cognitive interviews with cisgender women aged 18–49 in two US states ( N = 64) to assess these new approaches and questions for improving abortion reporting. Our findings suggest that including abortion as part of a list of other sexual and reproductive health services, asking a yes/no question about lifetime experience of abortion instead of asking about number of abortions, and developing an improved introduction to abortion questions may help to elicit more accurate survey reports. Opportunities exist to improve survey measurement of abortion. Reducing the underreporting of abortion in surveys has the potential to improve sexual and reproductive health research that relies on pregnancy histories.